2020
DOI: 10.1152/jn.00188.2020
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 induced upregulation of T-type Ca2+ currents and sensitization of DRG nociceptors is attenuated by MNK inhibition

Abstract: In this study, we show that the MNK inhibitor and anti-tumor agent eFT508 (tomivosertib) is effective in attenuating IL-6 induced sensitization of dorsal root ganglion (DRG) nociceptors. Pretreatment with eFT508 in DRG cultures from mice helps mitigate the development of hyperexcitability in response to IL-6. Furthermore, our data reveal that the upregulation of T-type voltage-gated calcium channels following IL-6 application can be blocked by eFT508, implicating the MNK-eIF4E signaling pathway in membrane tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 57 publications
0
22
2
Order By: Relevance
“…A study demonstrated that MKNK2 is involved in mechanisms of nociceptor plasticity and chronic pain development (Moy et al., 2017 ). And MKNK inhibition was shown to reduce sensitization of dorsal root ganglion nociceptors (Jeevakumar et al., 2020 ). The kinase MKNK2 was found by its interaction with the mitogen‐activated protein kinases (MAPKs), p38‐MAPK, and extracellular signal‐regulated kinase (ERK) (Waskiewicz et al., 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study demonstrated that MKNK2 is involved in mechanisms of nociceptor plasticity and chronic pain development (Moy et al., 2017 ). And MKNK inhibition was shown to reduce sensitization of dorsal root ganglion nociceptors (Jeevakumar et al., 2020 ). The kinase MKNK2 was found by its interaction with the mitogen‐activated protein kinases (MAPKs), p38‐MAPK, and extracellular signal‐regulated kinase (ERK) (Waskiewicz et al., 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, IL-1b, IL-6, PGE 2 , TNFa and CCL2 released by macrophages can stimulate specific cognate receptors on nociceptive neurons contributing to the development of neuropathic pain. 213,[251][252][253][254] Activated macrophages secrete HMGB1, which binds to TLR4 receptors on sensory neurons to play a role in the pathogenesis of neuropathic pain in animal models. 46,239,240 Hydrogen sulfide (H 2 S) is generated in activated macrophages and contributes to neuronal hyperexcitation by upregulating and activating neuronal calcium channels (transient receptor potential cation channel A1; TRPA1).…”
Section: Macrophage To Sensory Neuron Interactionsmentioning
confidence: 99%
“…Inhibition of MNKs with cercosporamide or genetic elimination of eIF4E phosphorylation attenuates mechanical hypersensitivity evoked by IL‐6 (Moy et al, 2017). Similarly, a blockade of MNKs with eFT‐508 interferes with the sensitization of nociceptors by IL‐6 (Jeevakumar et al, 2020). A second inflammatory mediator, nerve growth factor (NGF), stimulates mTOR and increases nascent protein synthesis (Melemedjian et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of MNKs with cercosporamide or genetic elimination of eIF4E phosphorylation attenuates mechanical hypersensitivity evoked by IL-6 (Moy et al, 2017). Similarly, a blockade of MNKs with eFT-508 interferes with the sensitization of nociceptors by IL-6 (Jeevakumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%